The Effect of Human Resources Development (HRD), Work Discipline and Work Environment on Employee Performance at the Regional Office of the National Land Agency Bengkulu Province - Weni Nopitasari; Karona Cahya Susena; Rina Trisna Yanti (Journal of Indonesian Management, 2021)
The purpose of this study was to determine the effect of Human Resource Development (HR), work discipline and work environment on employee performance at the Regional Office of the National Land Agency of Bengkulu Province. The analytical methods used include validity test, homepage linear regression, coefficient of determination, hypothesis testing (t test and f test). The results of the study show a positive regression direction with the equation Y = 2.156+ 0.281X1 + 0.341X2 + 0.323X3 with a positive regression direction, meaning that if the Development of Human Resources, Work Discipline and Work Environment has increased, the performance will also increase. a significant influence on the performance of the Regional Office of the National Land Agency of Bengkulu Province, this is evidenced by a significant value of 0.002 which is smaller than 0.05. Work Discipline has a significant effect on performance at the Regional Office of the National Land Agency of Bengkulu Province, this is evidenced by a significant value of 0.001 which is smaller than 0.05. The Work Environment has a significant influence on the Performance of the Regional Office of the National Land Agency of Bengkulu Province, this is evidenced by a significant value of 0.004 which is smaller than 0.05 Human Resource Development, Work Discipline and Work Environment have a significant effect together on the Performance of the Regional Office Bengkulu Province National Land Agency this is evidenced by a significant value of 0.000 which is smaller than 0.05.